PENGARUH BIMBINGAN KELOMPOK TERHADAP INTERAKSI SOSIAL SISWA DENGAN TEMAN SEBAYA PADA KELAS X DI SMA HANDAYANI PEKANBARU T.P 2014/2015 - Nisa, Dhiny Rahma Nisa Rahma; Arlizon, Raja Arlizon Raja; Yakub, Elni Yakub Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the social interaction of students before and after counseling groups and determine how much influence the group guidance on the level of social interaction of students in class X SMA Handayani Pekanbaru academic year 2014/2015. The problem in this research are: 1) Determine the level of the social interaction of students before group counseling services have given. 2) Determine the course of the implementation process of group counseling services to improve students' social interaction. 3) Knowing the students' level of social interaction after the group counseling serviceshave given. 4) Knowing the difference in the level of social interaction of students before and after group counseling services. 5) Knowing how much influence the group guidance services to the students' level of social interaction. This study uses the Pre-Experiment with patterns of one-group pretest-posttest. Population of this research is 206 student of class X SMA Handayani. The technique used is purposive sampling. The determination of the number of samples is 30 students who have the lowest social interaction. the result of this research based on t test obtained t at 18.43 and ttabel 2,000. So, test > table (18.43> 2.000). So Ho rejected and Ha accepted, which means that in this study there is a significant difference to improving the social interaction of students before the post given group counseling services. From the calculation of product moment correlation r xy = 0.78, coefficient determinant or r2 = 0.61, which means there is a 61% contribution to group counseling services increased social interaction in class X SMA Handayani Pekanbaru 2014/2015.Key Words: Guidance Group, Social Interaction Students